2001
DOI: 10.1063/1.1351862
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission yields from MgO deposited on carbon nanotubes

Abstract: Enormously high secondary electron emission yields under electric field are observed from MgO deposited on carbon nanotubes. The yields reach a value as high as 15 000 and are strongly dependent upon the bias voltage applied to the sample. The creation of the electric field across the MgO film after bombardment of primary electrons is considered as one of key features, since positive charges are generated at the surface by departure of secondary electrons. Subsequent bombarding electrons produce other secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…When incident electrons from the electron emitters strike the internal walls of the channel, secondary electrons are emitted from the surface. The FIU team and its collaborators have already observed that the secondary electron emission (SEE) yield increased enormously when electrons bombarded a very thin (~15-30 nm) MgO film deposited on highly conductive carbon nanotube surface [3]. The SEE yield as a function of the bias potential shows the emission yield can be as large as 15,000 secondary electrons per incident primary.…”
Section: B2 Carbon Nanotube Field Emittersmentioning
confidence: 99%
See 3 more Smart Citations
“…When incident electrons from the electron emitters strike the internal walls of the channel, secondary electrons are emitted from the surface. The FIU team and its collaborators have already observed that the secondary electron emission (SEE) yield increased enormously when electrons bombarded a very thin (~15-30 nm) MgO film deposited on highly conductive carbon nanotube surface [3]. The SEE yield as a function of the bias potential shows the emission yield can be as large as 15,000 secondary electrons per incident primary.…”
Section: B2 Carbon Nanotube Field Emittersmentioning
confidence: 99%
“…It is planned to first coat the inside surface of the channel wall with highly conductive material layer (such as electrodeless plated or sputtered Cu [3,4]), as shown in Fig. 3.…”
Section: B2 Carbon Nanotube Field Emittersmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesia layers has been increasingly noted for their advantages as a key element of plasma display panels (PDPs) [1][2][3][4][5]. It protects the dielectric layer above the electrodes from sputtering while yielding a high ion-induced secondary electron emission (SEE) coefficient.…”
Section: Introductionmentioning
confidence: 99%